PENGARUH PERBEDAAN USIA DAN GENDER ATASAN-BAWAHAN TERHADAP KOMITMEN ORGANISASI DAN KEPUASAN KERJA KARYAWAN GRAPARI TELKOMSEL JAKARTA - B. Medina Nilasari (Universitas Trisakti, 2008)
This study investigates the negative impact of age and gender diversity between supervisors-subordinate on job satisfaction and organizational commitment. The hypotheses were tested with a sample of 35 employees in Teikomsel Grapari West Jakarta Branch and 47 employees in Telkomsel Grapari South Jakarta Branch. Data were collected using quesioner and were analyzed using ANOVA. The result indicate that neither age differential and gender differential interaction were found that have no negative impact to job satisfaction and organizational commitment.Keyword : Age, gander, organizatinal commitmentjob satisfaction, telecommunication industry